2017
DOI: 10.1080/19490976.2017.1376162
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus vaccine response correlates with the infant gut microbiota composition in Pakistan

Abstract: Rotavirus (RV) is the leading cause of diarrhea-related death in children worldwide and ninety-five percent of rotavirus deaths occur in Africa and Asia. Rotavirus vaccines (RVV) can dramatically reduce RV deaths, but have low efficacy in low-income settings where they are most needed. The intestinal microbiome may contribute to this decreased RVV efficacy. This pilot study hypothesizes that infants' intestinal microbiota composition correlates with RVV immune responses and that RVV responders have different g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(185 citation statements)
references
References 45 publications
5
180
0
Order By: Relevance
“…Although the factors that determine the diminished effectiveness in less developed countries are not fully understood, both vaccines save more lives in low-income countries because of the higher rotavirus disease burden and mortality in these countries 90 . In Ghana and Pakistan, the intestinal microbiome composition has been associated with diminished efficacy of the RV1 vaccine 121,122 , although the exact implications of this are unclear. Environmental enteropathy (a common disorder in children in some low-income countries that is associated with diminished gastrointestinal immunity) might also have a role in reduced vaccine effectiveness in developing countries 123 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Although the factors that determine the diminished effectiveness in less developed countries are not fully understood, both vaccines save more lives in low-income countries because of the higher rotavirus disease burden and mortality in these countries 90 . In Ghana and Pakistan, the intestinal microbiome composition has been associated with diminished efficacy of the RV1 vaccine 121,122 , although the exact implications of this are unclear. Environmental enteropathy (a common disorder in children in some low-income countries that is associated with diminished gastrointestinal immunity) might also have a role in reduced vaccine effectiveness in developing countries 123 .…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Our results suggest that the observed richness decrease might be an outcome of the compound effect of the probiotic and the inflammatory effect of the adjuvant. An existing body of literature supports that probiotics and/or vaccination could result in modulation of the resident microbiome 45,46,47,13,18,48,49,50 . In addition, a significant decrease in richness and shift in the microbial community structure was also observed in association with the RB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that the microbiome greatly influences mucosal health 3,16 , but how vaccines, and any subsequent mucosal immune response, influence the microbiome is poorly understood 17 . There is increasing evidence that the immunogenicity and efficacy of current vaccines are related to the intestinal microbiome 18,19,20 . Multiple studies have also shown that probiotic administration prior to or concurrent with vaccination enhances B cell and antibody responses and provides the mucosa with direct protection from infection through interactions with the innate immune system 21,20,22,23 .…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of Pakistani and Dutch infants matched by age, sex, mode of deliver, birth weight and breastfeeding practices found no differences in diversity, richness or evenness, but reported higher Proteobacteria in Dutch infants including bacteria such as Enterobacter spp., E. coli, Serratia spp. and Klebsiella spp., 121 which goes against the notion that developed countries have lower enterobacteria. Similarly in a study of 65-70 Nigerian neonates, rectal swabbed samples consisted mainly of coagulase-negative Staphylococcus (38.6%), followed by S. aureus (31.4%) and E. coli (30%) on the first day of life.…”
Section: Hygiene Practices Impact the Ecological Succession Of Bactermentioning
confidence: 95%